Diagnosing Balamuthia mandrillaris Encephalitis With Metagenomic Deep Sequencing. Issue 5 (24th August 2015) - Wilson, Michael R.; Shanbhag, Niraj M.; Reid, Michael J.; Singhal, Neel S.; Gelfand, Jeffrey M.; Sample, Hannah A.; Benkli, Barlas; O'Donovan, Brian D.; Ali, Ibne K.M.; Keating, M. Kelly; Dunnebacke, Thelma H.; Wood, Matthew D.; et al.
<x xml:space="preserve">Abstract</x> Objective Identification of a particular cause of meningoencephalitis can be challenging owing to the myriad bacteria, viruses, fungi, and parasites that can produce overlapping clinical phenotypes, frequently delaying diagnosis and therapy. Metagenomic deep sequencing (MDS) approaches to infectious disease diagnostics are known for their ability to identify unusual or novel viruses and thus are well suited for investigating possible etiologies of meningoencephalitis. Methods We present the case of a 74‐year‐old woman with endophthalmitis followed by meningoencephalitis. MDS of her cerebrospinal fluid (CSF) was performed to identify an infectious agent. Results Sequences aligning to Balamuthia mandrillaris ribosomal RNA genes were identified in the CSF by MDS. Polymerase chain reaction subsequently confirmed the presence of B. mandrillaris in CSF, brain tissue, and vitreous fluid from the patient's infected eye. B. mandrillaris serology and immunohistochemistry for free‐living amoebas on the brain biopsy tissue were positive. Interpretation The diagnosis was made using MDS after the patient had been hospitalized for several weeks and subjected to costly and invasive testing. MDS is a powerful diagnostic tool with the potential for rapid and unbiased pathogen identification leading to early therapeutic targeting. Ann Neurol 2015;78:Ann Neurol 2015;78:679–696